Representation Of Urban American Women In Sex And The City Series : A Postfeminist Study - Abas, Nur Laila; , Dr. Phil. Dewi Candraningrum, M.Ed; , Drs. M. Thoyibi, M. S. (2013)
This research is aimed to show representation of Urban American Women presentation in Sex and the City series based on the postfeminist perspective. This research is done by establishing three intentions, the first is analyzing how Urban American women is represented, the second is analyzing the dominant ideology by using representation theory and the third is analyzing the construction of womanhood by using postfeminism theory .The study is a qualitative study. Type of data of the study is literary taken from two data sources: primary and secondary. The primary data sources taken from Sex and the City Series directed by Michael Patrick King and released in 1998. While the secondary data sources are materials taken from books and internet related to the study. Both data are collected through library research and analyzed by descriptive analyses. The study comes to the following conclusions. Based on the discussion of text and context the conclusion is Sex and the City is a romantic comedy television series which concern in the sexuality, sexually transmitted disease, fashion, and friendship, mostly through the conversation and voice over narration of four single New York women. Then, from the discussion of representation Sex and the City portray the urban American women in dealing with their single life, their lifestyle, their choice of fashion and their existence. The last from the discussion of the construction of womanhood it can be concluded that many feminist issues are tackled in the show, such as gender-bias, limited constructions of femininity, dependency, and prejudice against single women. From those conclusions are suitable the characteristic of postfeminist such as the modernity of the women, aggressiveness, sisterhood, sexual empowerment, power, self awareness, and choices. Therefore the researcher finds a dominant ideology that appears in Sex and the City series. It is the ideals of female subjectivity present in postfeminism, these ideals not only develop the belief but demand it as an indicator of success that women can be independent and successful individuals.